ETHICAL DYNAMICS IN CORPORATE GOVERNANCE: A GLOBAL PERSPECTIVE ON CORPORATE GOVERNANCE PRACTICES - Diva Aulia Ni`masari, Pinky Permata Sari (Integrative Perspectives of Social and Science Journal, 2025)
Corporate governance bears completely different characteristics in the major economies, with the presence of the regulatory frameworks, cultural parameters, and economic priorities being the factors determining these differences. The shareholder-centric model in the United States has rigorous financial regulations whereas, in the United Kingdom, the principles-based approach stretches flexibility but still demands accountability. Germany's stakeholder-oriented system with a two-tier board structure allows for the greatest representation, while Japan has made a transition from the keiretsu system to a mode of governance stressing more transparency. In China, state influence is overwhelmingly predominant in the setting of GCG priorities against the backdrop of the national interest. What remains common, notwithstanding these differences, is the ethical challenges of transparency, executive accountability, and regulatory enforcement. Corporate governance is bound to evolve against GCG challenges emerging globally in the economic and social